Aristotle on action and agency - Alanen, HS (2022)
Many consider Aristotle the father of philosophy of action. This sentiment is shared by contemporary philosophers with opposing views on action. The guiding question of this thesis is to determine what philosophy of action might look like for Aristotle by considering the questions Aristotle investigates, his philosophical framework within which he develops his answers, and the basic assumptions he makes in answering his questions. This requires investigating Aristotle’s views on capacities, nature, activities, affections, the relation between agents and patients, desire, and goodness. I argue that Aristotle’s approach to action emerges as a unique approach of its own.